Enjoying an empty edifice : nationalism through the lenses of Lacanian psychoanalysis - Blanuša, Nebojša (Array, 2021)
This paper reaffirms the methodological potentials of Lacanian psychoanalysis for the theories of nationalism. From the Lacanian perspective, national consciousness and self-determination are only possible in the fantasmatic framework through the (mis)recognition and retroactive construction. National imagination is the form of transference, necessary for performing the nation through invented traditions and rituals. However, beyond symbolization and imaginary (mis)recognition, there is always something that resists closure, linked with the subjects' desire and organized around the lack of the subjects' full enjoyment. Taking together all these aspects, we build an analytical framework for the study of nationalism, which comprises a quadruple system of identifications by referring to the concepts of Ideal-Ego, Ego-Ideal, Super-Ego and specular Other, and illustrate it through the example of the AKP's Turkish nationalism.